Drug Delivery Nanosystems for Cardiovascular Stents. (2017) - Bakola, V.; Karagkiozaki, V.; Pappa, F.; Tsiapla, A.R.; Pavlidou, E.; Moutsios, I.; A.Laskarakis,; Logothetidis, S.
Abstract: The treatment of Coronary Heart Disease has been revolutionised by the use of Arterial Stents. Arterial Stents, are small gridding gadgets, acting as a supporting scaffold into the arteries where the blood flow has become restricted at a dangerously point. There are three generations of Arterial Stents that have been evolved through the past decade. First were bare metal stents that evolved to polymer coated drug-delivery devices and, more recently, to fully biodegradable drug delivery designs. In this work, Drug Delivery Nanosystems of Polycaprolactone (PCL) and Polylactic acid (PLA) fibrous scaffolds were developed via Electrospinning process. The surface morphology and topography were evaluated via Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM) and Optical Microscopy. Further analysis has shown that the average fiber diameter is around 1200 nm and after Contact Angle (CA) measurements has justified the hydrophobic behaviour of those matrices. Drug release kinetics, along with Degradation Studies, revealed a sustained and controllable release of diverse drugs, through fibrous matrices along with time. The successful encapsulation of drugs through fiber-based scaffolds revealed a unique combined morphology and topography, with properties that control the pharmacokinetics in vitro, thus leading to a valuable tool towards atherosclerosis treatment.